Specificity of the School-Students’ Illegal Behavior Prevention in the Work of Social Teacher - BOCHELIUK, Vitalii I.; SHVETS, Tetiana M.; SHAPOSHNYKOVA, Iryna V.; SHAPOSHNYKOV, Kostiantyn S.; PANOV, Nikita S. (Journal of Advanced Research in Law and Economics, 2019)
The research analyzes and systematizes the social and pedagogical principles of adolescent delinquent behavior prevention in the social teacher work in the school-student environment at the present stage of society development. Leading approach to the study of this problem is the descriptive method that has afforded revealing peculiarities of the primary areas of work with adolescents with delinquent behavior which are primary and secondary prevention of offenses, social rehabilitation of juveniles, who had experience of illegal behavior and psychological and corrective work with them. The materials of the paper imply the practical significance for the university teachers of the pedagogical specializations.